Emergency Remote Teaching Experiences of Bangladeshi English Language Teachers in Pandemic (Feni University Journal, 2026)
Emergency Remote Teaching (ERT) approach arises when there is a sudden clog in teaching and learning physically. This study explores the emergency remote teaching experiences of English language instructors during the COVID-19 pandemic. The objective of this study was to examine teachers' adaptation strategies, technological challenges, and the impact of ERT on student engagement and learning outcomes. Through qualitative interviews and FGD with a diverse group of English language instructors, the study identifies key factors influencing the effectiveness of remote teaching, such as access to technology, digital literacy, and institutional support. The findings reveal that while teachers faced considerable obstacles, including limited resources and inadequate training, they exhibited resilience and creativity in overcoming these challenges. This study acknowledges some limitations such as the number of participants could be larger; data collection tools could be more diverse and broader. It also acknowledges that the result could be different if the students’ experiences were gathered. In conclusion, this study provides some recommendations for improving the preparedness of English language educators for future emergencies, focusing on the need for professional development, improved technological infrastructure, and more effective pedagogical frameworks for remote instruction.FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (253-268)